Proximate Composition and Sensory Properties Evaluation of Pandesal Produced from Squash (Cucurbita maxima) - Quijano, Richmon; Peñalber, Martina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to develop and evaluate pandesal produced from squash (Cucurbita maxima) fortified with Corn-Based Sagip Nutri Pack, focusing on its proximate composition, sensory properties, and economic feasibility. Anchored on nutrition improvement and food product innovation concepts, the study employed a quantitative true experimental research design. Four formulations were prepared, with three treatments (F2, F3, F4) subjected to nutrient analysis and sensory evaluation. Seventy-five purposively selected respondents assessed the product using a 9-point Hedonic Scale based on color/appearance, odor/aroma, taste/flavor, texture, and general acceptability, while statistical treatments included weighted mean, Analysis of Variance (ANOVA), and Tukey’s HSD test. Results revealed that increasing levels of Corn-Based Sagip Nutri Pack significantly enhanced protein, fiber, lipid, ash, and energy content while reducing moisture, with F4 yielding the highest nutritional values. However, F2 obtained the highest acceptability ratings across all sensory attributes. Economic analysis showed that F1 and F2 achieved the highest return on expenses, indicating better financial feasibility compared to higher fortification levels. The study concluded that squash pandesal fortified with Corn-Based Sagip Nutri Pack is a viable and nutritionally beneficial alternative to conventional bread, with F2 providing the most balanced outcome in terms of acceptability, nutrition, and cost efficiency. It is recommended for use in school feeding programs and as a nutritious snack option. The study aligns with Sustainable Development Goals such as SDG 2 (Zero Hunger) and SDG 3 (Good Health and Well-being), as it promotes improved nutrition and accessible healthy food options. Its sustainability impact lies in supporting community nutrition interventions, enhancing food innovation using local resources, and contributing to efforts in reducing malnutrition among school-aged children.